STRATEGI PENGEMBANGAN BALAI PENELITIAN DAN PENGEMBANGAN KESEHATAN BANJARNEGARA - Agung Puja Kesuma; Laksono Trisnantoro; Yodi Mahendrahata (Journal of Health Service Management, 2021)
Background: Based on Permenkes No. 65 the year 2017, the Banjarnegara Health Research and Development (R&D) Unit is one oft he units under the NIHRD Ministry of Health, which has the task of conducting research and development of health with the advantage of leptospirosis control. The working area includes four provinces: DI Yogyakarta, DKI Jakarta, West Kalimantan, and South Sulawesi. In addition to conducting excellent research, Banjarnegara Health R&D Unit also has to do health research based on program needs in the target area. The Banjarnegara Health R&D Unit needs to understand its strengths, weaknesses, opportunities, and challenges through the identification of internal and external environments that can be using as a basis for developing strategic planning for organizational development. Objective: Formulate alternative strategies for the development of The Banjarnegara Health R&D Unit. Methods: Research A descriptive case study by using a holistic single case design plan. Variable research is the internal and external factor of Banjarnegara Health R&D Unit, development issues, and the strategies of develepment. Data obtained through in-depth interviews with the related informants, observation, and study of documents. Results: Internal environmental analysis to see the strengths and weaknesses of the Banjarnegara Health R&D Unit. Based on the results of internal environmental analysis, the Banjarnegara Health R&D Unit has considerable strength in terms of organizational as pects, HR experience, a budget that continues to increase every year, and infrastructure. External environmental analysis opportunities that can be utilized by the Banjarnegara Health R&D Unit are excellent stakeholder support, opportunities to collaborate with various institutions, sources of research funding, availability of information technology, and regulations that support the research climate. While the threats identified, require large budgets to keep abreast of medical or laboratory equipment technology, the development of potential epidemic diseases, limited recruitment of human resources and the potential to reduce PNBP. Conclusion: Strategies that can be used Banjarnegara Health R&D Unit for development are the development of services and products according to the needs of the stakeholders, the development of cooperation with strategic stakeholders, and the development of organizations with public service agency financial management patterns.